Prospects for the Construction of the Poseidon Gas Pipeline as a Factor in Supplying the Needs of the Southern Europe Countries with Natural Gas - Khalova, Gyulnar Osmanovna; Illeritskiy, Nikita Igorevich; Smirnova, Vera Alekseevna (International Journal of Energy Economics and Policy, 2018)
The EU is one of the largest energy consumers in the world. However, it faces issues of high fuel import dependency, energy resources import diversification, lack of pipeline infrastructure, etc. There are several ways to improve EU's energy sector by wider use of natural gas (NG). Such projects as ITGI-Poseidon, TANAP, TAP, TurkStream and others may provide necessary capacities. Turkey plays an important role as a transit country for NG supplies and in the future it can become one of the key gas hubs in the south-eastern part of Europe, as it occupies a strategically advantageous geographical position. This paper reviews the main economic development and energy sector indicators of the EU, along with current and future NG supply and transit projects. It is stated energy cooperation between Russia, Turkey and the EU is essential for sustainable development of both EU and Turkey energy sector. Hence, recommendations for NG sector development and further energy cooperation with Russia are provided. Keywords: Natural Gas, Energy Supply, Energy Cooperation JEL Classifications: Q3, Q4 DOI: https://doi.org/10.32479/ijeep.7093